High blood pressure in school children and adolescents in Argentina over the past 25 years: A systematic review of observational studies - Diaz, Alberto Alejandro (2017)
Over the past years, hypertension has been recognized as an important health problem in the pediatric population. A systematic review of observational studies published between 1988 and 2014 was conducted to estimate the prevalence of high blood pressure and cardiovascular risk factors among children and adolescents in Argentina.POPULATION AND METHODS:A bibliographic search was done in MEDLINE, SciELO, and LILACS to look for studies on high blood pressure prevalence in school children and adolescents in Argentina. Studies and surveys that had included the measurement of blood pressure in children and adolescents (aged 5-20 years) according to the Fourth Report on the Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents by the American Academy of Pediatrics were included in this study.RESULTS:Fourteen publications were identified. The pooled prevalence in 11 706 subjects (random effects model) was 6.61% (95% confidence interval [CI]: 4.30-9.37). The crude prevalence was 7.35% (95% CI: 6.88-7.83). High blood pressure was more prevalent among adolescents than children ≤ 10 years old (7.4% versus 4.3%, P = 0.001), and among boys than girls (11.2% versus 6.8%, P = 0.001). The most common risk factors included a sedentary lifestyle (50%), overweight (15.4%), abdominal obesity (13.7%), obesity (11.5%), and smoking (6.5%).CONCLUSIONS:Our data show that the prevalence of high blood pressure and cardiovascular risk factors in school children and adolescents is high, and this accounts for a very important public health problem in Argentina.